Shifts in Privacy Concerns - Goldfarb, Avi; Tucker, Catherine (American Economic Review, 2012)
This paper explores how digitization and the associated use of customer data have affected the evolution of consumer privacy concerns. We measure privacy concerns by reluctance to disclose income in an online marketing research survey. Using over three million responses over eight years, our data show: (1) Refusals to reveal information have risen over time, (2) Older people are less likely to reveal information, and (3) The difference between older and younger people has increased over time. Our results suggest that the trends over time are partly due to broadening perceptions of the contexts in which privacy is relevant.